2018
DOI: 10.22492/ije.6.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Factors as Determinants of Self-efficacy and Resilience among Selected Filipino Child Development Workers

Abstract: This descriptive associative study focused on work-related factors as determinants of selfefficacy and resilience among 58 purposively-sampled Child Development Workers (CDWs). It specifically aims to profile the CDWs based on various work-related variables, to determine their psychosocial needs, resources, levels of self-efficacy and resilience, and to verify the association and relationship of these variables in relation to self-efficacy and resilience. A questionnaire, comprised of questions on perceived ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Escarlos, Bermillo, Magday, and Salon (2019) investigated the impact of mentoring barangay day care workers and found that the extension program improved the instructional services of day care workers. Del Rosario et al (2018) enumerated few studies about DCCs and DCWs, including Abulon's (2013) barangay day care center status survey in the country where results showed that the emergence of the day care centers in the country proved the states' deepening commitment to uphold early childhood education. Cadosales' (2011) analysis of DCWs' teaching needs such as teaching reading, teaching number concepts, teaching strategies, production of instructional materials and pedagogy and Reyes' (1996) study of variables affecting day care policy implementation in one of the Philippine regions found that critical variables (such as output, environment, organization, process) and constraints (like financial constraints in the implementation of the basics of the day care law, lack of concern on the part of the local government units (LGUs) for the pursuit of a genuine day care service program mismatch the LGU's capacity to satisfy the demands of the day care law in the framework of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Escarlos, Bermillo, Magday, and Salon (2019) investigated the impact of mentoring barangay day care workers and found that the extension program improved the instructional services of day care workers. Del Rosario et al (2018) enumerated few studies about DCCs and DCWs, including Abulon's (2013) barangay day care center status survey in the country where results showed that the emergence of the day care centers in the country proved the states' deepening commitment to uphold early childhood education. Cadosales' (2011) analysis of DCWs' teaching needs such as teaching reading, teaching number concepts, teaching strategies, production of instructional materials and pedagogy and Reyes' (1996) study of variables affecting day care policy implementation in one of the Philippine regions found that critical variables (such as output, environment, organization, process) and constraints (like financial constraints in the implementation of the basics of the day care law, lack of concern on the part of the local government units (LGUs) for the pursuit of a genuine day care service program mismatch the LGU's capacity to satisfy the demands of the day care law in the framework of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration the multitude functions of childhood workers and the laborious nature of childcare profession, resilience and self-efficacy are variables also found to be essential among professionals working with young children. Resilience is substantial in discovering professional satisfaction amidst stressful work environments, while self-efficacy is influenced by professional experience, collaboration and engagement among learners (del Rosario et. al., 2018).…”
mentioning
confidence: 99%